Cost-effectiveness analysis of natural birth and elective C-section in supplemental health - Aline Piovezan Entringer; Márcia Pinto; Maria Auxiliadora de Souza Mendes Gomes (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To conduct a cost-effectiveness analysis of natural childbirth and elective C-section for normal risk pregnant women. METHODS The study was conducted from the perspective of supplemental health, a health subsystem that finances private obstetric care, represented in Brazil by health plan operators. The reference populations were normal risk pregnant women, who could undergo natural childbirth or elective C-section, subdivided into primiparous and multiparous women with previous uterine scar. A decision analysis model was constructed including choice of delivery types and health consequences for mother and newborn, from admission for delivery to maternity hospital discharge. Effectiveness measures were identified from the scientific literature, and cost data obtained by consultation with health professionals, health plan operators' pricing tables, and pricing reference publications of health resources. RESULTS Natural childbirth was dominant compared with elective C-section for primiparous normal risk pregnant women, presenting lower cost (R$5,210.96 versus R$5,753.54) and better or equal effectiveness for all evaluated outcomes. For multiparous women with previous uterine scar, C-section presented lower cost (R$5,364.07) than natural childbirth (R$5,632.24), and better or equal effectiveness; therefore, C-section is more efficient for this population. CONCLUSIONS It is necessary to control and audit C-sections without clinical indication, especially with regard to primiparous women, contributing to the management of perinatal care.